Forecast of the Demografic Development of Russia - Chichkanov, Valeriy Petrovich; Vasilyeva, Aleksandra Vladimirovna; Bystray, Gennadiy Pavlovich; Okhotnikov, Sergey Aleksandrovich (Economy of Regions, 2015)
In the article, the contemporary issues of the reproduction of the Russian population, their reasons, and state policy toward them are considered. Relevance of the task solution of assessment of the most expected birth rate dynamics of the Russian population in future in the conditions of low norms of the parenthood status taking into account the influence of government measures for the birth rate stimulation is proved. In order to achieve this objective, on the basis of the behavior probability distribution function of crude birth rate, the probabilistic assessment of the future birth rate dynamics of the Russian population was conducted. On the basis of the modernized Hirst method, two expected dynamics trajectories of crude birth rate were constructed: the first trajectory corresponds to the scenario at which the value of crude birth rate will be in the range of 8-10,5 born / 1000 people (probability - 0,182), including the negative external impact, the second trajectory will be in the range of 13-16,5 born / 1000 people (probability - 0,618), including the positive external impact. In spite of the fact that these scenarios are quite different, the dynamics trajectories of crude birth rate predicted according to them during the period of 2015-2041 that corresponds to the time of the reliable prediction are almost identical. The analysis of the received results enabled to conclude that the state population policy cannot affect the future dynamics of the birth rate due mainly to to the conjectural changes. These conclusions confirm the intellectual vested interest of the academic circles that government regulation of a demographic situation in Russia has to be aimed, first of all, at the health improvement and increase of the expected life interval of the population.